Geographic variation in and contextual factors related to biguanide adherence amongst medicaid enrolees with type 2 Diabetes Mellitus - Vincent Learnihan; Ralf-D. Schroers; Philip Coote; Marcus Blake; Neil T. Coffee; Mark Daniel (Elsevier, 2022)
Much is known about the adverse impacts on diabetes outcomes of non-adherence to diabetes medication. Less is known about how adherence to diabetes medication varies geographically, and the correspondence of this variation to social and contextual factors. Using pharmacy claims data over a two-year period, this study analysed non-adherence to biguanide medication for N=24,387 adult Medicaid enrolees diagnosed with Type 2 Diabetes Mellitus (T2DM) and residing in Ohio. Spatial analysis was used to detect clusters of census tract level rates of non-adherence, defined as the proportion of patients below the Proportion Days Covered (PDC) threshold of 80%, the level at which patients have a reasonable likelihood of achieving most clinical benefit from their medication. Multilevel models were used to understand associations between medication non-adherence and contextual factors including social vulnerability, urbanicity and distance to utilised pharmacy, with adjustment for individual-level covariates. These findings indicate that contextual factors are associated with medication non-adherence in Medicaid clients with T2DM. They suggest a need for spatially specific, multifaceted intervention programmes that target and/or account for the features of residential settings beyond individual and health system-level factors alone. While "environmental" considerations are often acknowledged, few intervention initiatives are predicated on explicit knowledge of spatially variable influences that can be targeted to enable and support medication adherence.